Relevance of DNA barcodes for biomonitoring of freshwater animals - Elías-Gutiérrez, Manuel; Valdez-Moreno, Martha (Frontiers in Environmental Science, 2023)
The COI gene, colloquially named the DNA barcode, has become a universal marker for species identification. There are different standardized markers for plants and fungi. Nevertheless, due to the taxonomic impediment, there are various proposals for Molecular Operational Taxonomic Units (MOTUs) because high-throughput sequencers can generate millions of sequences in one run. In the case of freshwater systems, it is possible to analyze entire communities through their DNA using just water or sediment. Using DNA barcodes with these technologies is known as metabarcoding, and it is based on environmental DNA (eDNA). More than 90% of studies were based on eDNA work with the MOTUs, without previous knowledge of the biodiversity in the studied place. Despite this problem, it has been proposed as the future of biomonitoring. All these studies are biased towards the global North and focused on freshwater macrofaunae. Few studies comprised other communities, such as zooplankton or phytoplankton. The future for biomonitoring should be based on a standardized gene, for example, COI, the most studied in animals, or another secondary consensual gene. Here we analyzed some proposals with 28s or 12s. The studies on eDNA can focus on analyses of the whole community or searching for a particular species. The latter can be an endangered species or an exotic. Any eDNA study focused on a community study should always involve the previous construction of a well-documented DNA baseline linked to vouchered specimens. Otherwise, it will be tough to discriminate between false positives and negatives. Biomonitoring routines based on eDNA can detect a change in a community due to any perturbation of the aquatic ecosystem. Also, it can track changes along the history of an epicontinental environment through the analyses of sediments. However, their implementation will be complex in most megadiverse Neotropical countries due to the lack of these baselines. It was demonstrated that a rapid construction of a baseline is possible, and later working on the curation of the species. However, there is no interest in their governments in this kind of research and the subsequent biomonitoring.